The Scholars Project: Maine's Distance Education Model for Preparing Early Childhood Special Educators to Work With Young Children With Disabilities. (June 2017) - Rooks-Ellis, Deborah L.
The Early Childhood Opportunity (EChO) Scholars project was designed to address the following significant needs in Maine: (a) prepare highly qualified early interventionists and early childhood special educators through distance education, (b) develop a system of support through a mentor network, (c) provide a graduate-level early childhood special education (ECSE) curriculum emphasizing current evidence-based practices (EBPs), and (d) develop a feedback loop designed to assess candidate knowledge, skills, and implementation of EBPs. This article describes the results of a 4-year Office of Special Education Programs project designed to support early childhood special educators across rural Maine. Key program components, successes, and future directions for continuous improvement are highlighted.